2018
DOI: 10.1007/978-3-319-91929-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysics with Radioactive Isotopes

Abstract: Radioactivity was discovered as a by-product of searching for elements with suitable chemical properties. Understanding its characteristics led to the development of nuclear physics, understanding that unstable configurations of nucleons transform into stable end products through radioactive decay. In the universe, nuclear reactions create new nuclei under the energetic circumstances characterising cosmic nucleosynthesis sites, such as the cores of stars and supernova explosions. Observing the radioactive deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…3 Many details that are beyond the scope of this review can be found in Branch and Wheeler (2017); Diehl et al (2018) books and in Thielemann et al (2018). 4 This amount of energy is often referred as 1 Bethe.…”
Section: Supernova Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…3 Many details that are beyond the scope of this review can be found in Branch and Wheeler (2017); Diehl et al (2018) books and in Thielemann et al (2018). 4 This amount of energy is often referred as 1 Bethe.…”
Section: Supernova Taxonomymentioning
confidence: 99%
“…Thermonuclear explosions in binary systems containing a white dwarf are delayed up to this point, and thereafter they inject important amounts of iron peak elements to the ISM causing a progressive reduction of [α/Fe] as metallicity increases. See Iliadis (2007); Diehl et al (2018); Thielemann et al (2018); Arnould and Goriely (2020) for recent overviews of nucleosynthesis in different astronomical sites.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma rays have been understood to be an excellent diagnostic of SNeIa for nearly five decades (e.g., [9,13]). In contrast to UVOIR emission, the escaping nuclear radiation is a direct consequence of the nuclear physics that governs the structure and dynamics of these objects and is encoded with critical fundamental evidence that can travel great distances unscathed.…”
Section: What Are Their Progenitor Systems? Why Do They Explode? How ...mentioning
confidence: 99%
“…Nuclear elements abundance in the universe are promoted by different astrophysics sites. The nuclear reactions re-arranges the basic constituents of atomic nuclei using different allowed configurations, where particle captures and photon nuclei emission are important mechanisms [1]. In addition when neutrinos flux are present they are also captured and emitted by 𝛽−decay of the involved nuclei.…”
Section: Introductionmentioning
confidence: 99%